Heat Transfer Investigations in Thermally Activated Battery – Experimental and Numerical Studies - Marek PREISKORN (Wojskowa Akademia Techniczna, 2012)
In this paper both experimental and numerical studies of heat transfer in thermally activated batteries deriving from chemical sources of electric currents are considered. These batteries are used to supply special devices in the army, i.e. missiles, rockets and they are characterized by the activation time from 0.1 s to several seconds with an effective working time from seconds, to tens of minutes [1]. The heat being generated during their work inside the battery causes a temperature increase of up to 873 K. In the frame of this work both experimental and numerical investigations of temperature distribution on the outer surface of the thermally activated battery BTR-03, as well as the heat flux distribution were carried out [8]. Comparing the temperature histories at several points on the outer surface of the battery BTR-03, obtained from experiment and calculated numerically allowed to validate the numerical model of heat transfer in the battery.
Keywords: Wymiana ciepła w baterii aktywowanej termicznie